Growth Performance, Carcass Characteristics and Organoleptic Properties of Broiler Chickens Fed Diets Containing Garlic and Turmeric Powder Mixture - R. A., Oluwafemi; O.C.P., Agubosi; Olatunji, Azeezat Olayinka; Hauwa, Sadiq; J. O, Alagbe (American Journal of Botany and Bioengineering, 2026)
A study was conducted to evaluate the effect of dietary inclusion of garlic (Allium sativum) and turmeric (Curcuma longa) powder mixture at ratio 1:1 on the growth performance, carcass characteristics and organoleptic properties of broiler chickens. A total of one hundred and fifty (150) day old (Arbor Acres) broiler chicks were randomly allotted into five dietary treatments in a completely randomised design (CRD). Each treatment was replicated three times, with ten birds per replicate. A basal diet was formulated to meet the nutrient requirement of broiler chicks and served as the control diet (treatment 1). Birds on treatments 2, 3, 4, and 5 were fed the basal diet with garlic and turmeric powder mixture at 0.2g, 0.4g, 0.6g, and 0.8g inclusion levels, respectively. Feed and clean water were provided ad-libitum throughout the experimental period, which lasted for 56 days. Data were collected on growth performance and carcass characteristics. Results of phytochemical composition show alkaloids (6.22%), terpenoids (5.78%), flavonoids (12.12%), phenols (4.67%), saponins (3.09%), oxalates (0.21%), and tannins (7.88%). The result of the growth performance showed a significant difference (P < 0.05) in body weight gained, final weight gained, average weight gained and feed conversion ratio. Carcass characteristics showed live weight (g), thighs (g), wings (g), kidneys (g), necks (g), breasts (g), and hearts (g), with a higher significant difference (P<0.05) in the 0.8g dietary treatment. The dressed weight (g) and dressing percentage indicated a higher significant difference (P<0.05) in 0.6g dietary treatment than 0.8g, 0.4g, 0.2g, and control diet. Weights of leg, bile, spleen, back, and head revealed no significant effect (P>0.05) across the dietary treatment. The organoleptic quality test revealed a significant difference (P<0.05) in juiciness between the dietary treatments while no variations (P>0.05) between 0.8g, ,0.6g, and 0.4g groups. The general acceptability indicated no differences (P>0.05) across the dietary treatments. Hence the results obtained from this research can be recommended for the inclusion of a garlic and turmeric powder mixture up to 0.8 g which improves growth performance, and overall quality of meat; this implies that they can be recommended to farmers in place of antibiotics and growth promoters.